Business process and software architecture model co-evolution patterns - Jamshidi, P.; Pahl, C. (2012 4th International Workshop on Modeling in Software Engineering (MISE), 2012)
Software systems are subject to change. To embrace change, the systems should be equipped with automated mechanisms. Business process and software architecture models are two artifacts that are subject to change in an interrelated manner that requires them co-evolve. As opposed to the traditional batch-based model transformation, we propose a comprehensive set of structural and behavioral evolution patterns that enable to incrementally reflect the impact of change of business processes to their associated architecture models by applying reusable patterns. A basis for automation is provided through a graph-based formalism.